2019
DOI: 10.3390/microorganisms7010024
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma boninense Disease of Oil Palm to Significantly Reduce Production After 2050 in Sumatra if Projected Climate Change Occurs

Abstract: Palm oil is a valuable crop. This relates to the high economic return from sales of the commodity, where Indonesia is the major producer in the world and the island of Sumatra is the most important region for palm oil production in the country. The island can be considered as a model for other oil palm growing regions in SE Asia. The area in Sumatra with a suitable climate for growing oil palm will decrease in size due to projected climate change as demonstrated specifically herein. The more unsuitable climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 17 publications
0
68
0
5
Order By: Relevance
“…The incidence of BSR for Papua New Guinea is considerably less than that predicted for other situations in, for example, (a) Sumatra, Indonesia (Paterson, 2019a) and (b) Thailand, and Myanmar (see below). The percentage of living OP which did not have BSR was predicted to be 36% (Table 1) by 2100.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The incidence of BSR for Papua New Guinea is considerably less than that predicted for other situations in, for example, (a) Sumatra, Indonesia (Paterson, 2019a) and (b) Thailand, and Myanmar (see below). The percentage of living OP which did not have BSR was predicted to be 36% (Table 1) by 2100.…”
Section: Discussionmentioning
confidence: 81%
“…In Thailand, most of the highly suitable climate was in the south (Paterson et al, 2015(Paterson et al, , 2017. The large increase in marginal climate predicted for Thailand would be detrimental to the The incidence of BSR was considered very high in the future for Sumatra, Indonesia (Paterson, 2019a) and peninsular Malaysia (Paterson, 2019b) using similar methods to those described herein.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(Idris et al 2011). Paterson (2019) reported that the disease is increasing in inland Peninsular Malaysia and also Sabah, Malaysia, and in some cases at high levels, whereas it has not been detected before. Several attempts have been made to control BSR using various control methods; however to date, none of the methods gave promising results in management of Ganoderma boninense, the major causal pathogen of BSR disease (Ariffin et al 2000;Sanderson et al 2000;Susanto et al 2005).…”
Section: Introductionmentioning
confidence: 88%